1997
DOI: 10.1097/00004647-199709000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric Oxide Synthase Activation by Vasoactive Intestinal Peptide in Bovine Cerebral Arteries

Abstract: Summary:The partIcipation of nitric oxide and vasoactive intestinal peptide (VIP) in the neurogenic regulation of bovine cerebral arteries was investigated, Nitrergic nerve fibers and ganglion-like groups of neurons were revealed by NADPH diaphorase staining in the adventitial layer of bovine cerebral arteries, NADPH diaphorase also was present in endothelial cells but not in the smooth muscle layer. Double immunola beling for neuronal nitric oxide synthase and VIP indicated that both molecules co-localized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…NE acts more likely on presynaptic adrenoceptors located on nitrergic nerves to cause release of NO, which then induces vasodilation. This conclusion is consistent with the reported biochemical findings that neurogenic vasodilation in cerebral arteries from different species induced by either TNS or nicotine is accompanied by an increase in cGMP but not cAMP (15,37,38), suggesting that the terminal transmitter acting on the smooth muscle to induce a relaxation is NO (known to increase cGMP synthesis) or a related substance but not NE (known to increase cAMP synthesis via its b -adrenoceptor action) (Fig. 1).…”
Section: Nicotine-induced No-mediated Cerebral Neurogenic Vasodilatiosupporting
confidence: 92%
“…NE acts more likely on presynaptic adrenoceptors located on nitrergic nerves to cause release of NO, which then induces vasodilation. This conclusion is consistent with the reported biochemical findings that neurogenic vasodilation in cerebral arteries from different species induced by either TNS or nicotine is accompanied by an increase in cGMP but not cAMP (15,37,38), suggesting that the terminal transmitter acting on the smooth muscle to induce a relaxation is NO (known to increase cGMP synthesis) or a related substance but not NE (known to increase cAMP synthesis via its b -adrenoceptor action) (Fig. 1).…”
Section: Nicotine-induced No-mediated Cerebral Neurogenic Vasodilatiosupporting
confidence: 92%
“…Numerous histochemical and immunohistochemical studies have demonstrated that innervation of nitrergic nerves in the cerebral arteries are also observed in the guinea pig (Saito and Goto, 1994;Barroso et al, 1996), cat (Ayajiki et al, 1994;Kimura et al, 1997), monkey (Yoshida et al, 1994a;, pig (Sienkiewicz et al, 1995;Tanaka et al, 1999), cow (Toda and Okamura, 1996b;Gonzalez et al, 1997), sheep (Matthew, 1997), and human Gorelova et al, 1996). Porcine pial veins are also innervated by neurons containing NADPH diaphorase (Ishine et al, 1999).…”
Section: Prejunctional Modulation Of Nitrergic Nerve Function By Cholmentioning
confidence: 99%
“…Thus, inhibition of NO synthesis results in the attenuation of VIPinduced vasodilation of endothelium-denuded sheep middle cerebral arteries (Gaw et al, 1991) and bovine cerebral arteries (Gonzalez et al, 1997). In addition, the relaxant effect of VIP on isolated rat basilar arteries is inhibited by o-conotoxin or 7-nitroindazole (7-NI), showing that nitrergic neurons are activated by VIP (Seebeck et al, 2002).…”
Section: Introductionmentioning
confidence: 99%